Modelling and in silico simulation of human induced pluripotent stem cell derived cardiomyocyte electro-mechanical properties. (10th June 2022) - Folkmanaite, M; Zhou, X; Margara, F; Zaccolo, M; Rodriguez, B
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): BHF Background: Human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CM) enable accessible human data-based cardiology studies. However, a caveat in hiPSC-CM-based studies is their immature electrophysiological and contractile phenotype. One of the modifications occurring during hiPSC-CM maturation is the change in myofilament calcium sensitivity, an important indicator of cardiac muscle function [1, 2]. In silico hiPSC-CM investigations could help improve understanding of the hiPSC-CM-specific contractile behaviour and its changes during maturation. Considering the growing use of hiPSC-CM, it is vital to enable investigations of hiPSC-CM-specific contractile features. Purpose: To address the need of hiPSC-CM model with integrated contractile element, our goal is to develop an electromechanical human data-based iPSC-CM computer model. We aim to use the model to investigate the effects of the changes in myofilament calcium sensitivity on hiPSC-CM electrophysiology and contractility. Methods: We coupled a published hiPSC-CM electrophysiological model [3] with a model of the human adult cardiomyocyte contractile machinery [4] by linking intracellular calcium and calcium-bound troponin dynamics. The established electromechanical hiPSC-CM model was calibrated using experimental hiPSC-CM active tension data and its simulated electromechanical biomarkers were also evaluated against experimental action potential and calcium transient data. We conducted a sensitivity analysis to investigate the effects of changes in myofilament calcium sensitivity on the electrophysiology and contractility of the cell. Results: First, we demonstrated that the model successfully reproduces the hiPSC-CM contractile phenotype. Simulations showed a peak twitch tension of 0.44 kPa which takes 201 ms to peak and 164 ms to achieve 50% relaxation, which all agree with the experimental hiPSC-CM values. Simulated calcium transient and action potential biomarkers remain within the experimentally established ranges after electromechanical coupling. The sensitivity analysis of the hiPSC-CM model focused on the myofilament calcium sensitivity effects showed an increase in active tension amplitude with a decrease in calcium transient peaks upon increased myofilament calcium sensitivity. Large increases in myofilament calcium sensitivity result in depolarization failure with low amplitude fluctuations of membrane voltage, calcium transient and active tension. Altogether simulation results demonstrate the usability of the model for simulating and exploring not only physiological, but also pathological cardiac conditions. Conclusions: We present a new electromechanical hiPSC-CM model for in silico hiPSC-CM-based studies. The model has been evaluated against experimental data and has demonstrated the capacity to generate key electrophysiological currents, active tension as well as myofilament calcium sensitivity-induced electromechanical abnormalities.